Preparation and Characterization of Inclusion Complexes between Starch and P-Carotene - Febrina Butarbutar, Helen
13-Caroten is a carotenoid compound which is the main source of pro-Vitamin A_ 13-Caroten is a red-orange dominant color pigment and naturally found in plants and fruits that it can be used as food coloring_ As hydrophobic molecule, 13-caroten can be complexed with starch, to form inclusion complexes. In this research, the starch was isolated from cassava with 30% yield containing 18,2% amylose. The starch was then mixed with 13-caroten at 85 oc with complexation time of 0, 2, 4, 6 hours with 18 hours additional heating which produces optimum result, and 6 hours without an additional heating 13-Caroten content was varied at 10%, 30%, and 50% based on weight starch (%w/w) _ The result of complexes were characterized with FTIR (Fomier-Transform Infrared Spectroscopy), XRD (X-Ray Powder Diffraction), SEM (Scanning Electron Microscopy), TGA (Thermogravimetric Analysis Differential Scanning Calorimetry), and PSA (Particle Size Analyzer)_ From FTIR, the absence of the vibration guest molecule deals of the indicates that 13-caroten has been encapsulated inside the amylose helices. The XRD results should that the complexes had a difraction 28 peak ou of 18,2 °, 30% complex at 18,8 °, and 50% complex at 18,7 o SEM characterization shows that the complex has different morphology compared to uncomplexed starch and 13-caroten This difference may be due to heating process and different amounts of added guest molecules. From TGA, The 10% complex starts to degrade at 250--356 °C, while 30% complex at 256---372 °C, and 50% complex at 262-389 o c_ The resulting complexes have diameters of 44,5 l1ITl, 667 nm, and 747 nm for 10%, 30%, and 50% complexes respectively measured by PSA Degradation test conducted for starch-13-caroten complex using a-amylase shows decreases in the enzyme's activity compared to that of the uncomplexed starch_ It indicates that the structmes of using the resulting complexes slow down the starch degradation This result is suppmted by slower enzyme kinetics of using starch-13-caroten complexex as substrates compared to that of starch only